HALF-COMPETITION TENNIS MATCH RULES WITH THE COUNT OF THE BEST POOL CHAMPION - Rices Jatra; Rezki Rezki; Raffly Henjilito; M. Ikhsan; Firdaus Firdaus (Universitas Negeri Padang Press, Pusat Kajian Pendidikan Olahraga, Kesehatan dan Rekreasi, Fakultas Ilmu Keolahragaan, Univeristas Negeri Padang., 2021)
The development of tennis tournaments during the COVID-19 pandemic has become one of the sports that is in demand by many people. This is because tennis, which is played without body contact, is considered one of the sports that has little impact on the spread of COVID-19. Therefore, the tournament was held to keep the body's immunity fit and away from covid 19. For an effective and fair play tournament, it needs to be regulated with mature techniques and not all participants understand this. So for that we held a PKM activity with the title